Extent of awareness and prevalence of adulteration in selected food items in rural Dehradun - Srivastava, Ashok Kumar; Semwal, Jayanti; ., Deepshikha; Vyas, Shaili; Juyal, Ruchi (Indian Journal of Community Health, 2016)
Background: Adulteration of food items is common phenomenon in India. It includes both willful adulteration to improve texture and quality of food items and supply of substandard food items. The usual outcomes is outbreak of food borne illness. Aims & Objectives: i) To estimate the prevalence of food adulteration in selected food items ii) the awareness of subjects regarding food adulteration act and iii) their buying practices. Material and Methods: Samplesize:150 households was sampled, based on prevalence of adulteration to be around 50%, with 95% confidence interval and absolute allowable error of 10%. Sample household were drawn from the selected villages randomly. Pre-designed and pretested questionnaires was administered to fulfill the objectives and food items were tested using NICE food adulteration kit. Data were analyzed by numeral with percentage, Pearson’s correlation test and F test. Results: In 59.3% households, housewives purchased the food items for the house. The prevalence of adulteration ranged from 17.3% to 66.2% in selected food items. Loose product was purchased by 54.3%. The food labels on packed items was not read by 86.3%. Mean percentage of purity was highest among literates (57.3 ±12.3) than illiterates and those having primary education. Statistically significant F ratio was seen for mean percentage of purity and respondent’s literacy status. Conclusion: Adulterant is rampant in poor strata of society due to consumer’s illiteracy and lack of awareness towards food safety rules.